Metagenomic study reveals hidden relationships among fungal diversity, variation of plant disease, and genetic distance in Cornus florida (Cornaceae) - Pais, Andrew; Ristaino, Jean; Whetten, Ross; Xiang, Qiu-Yun (Jenny) (Frontiers in Plant Science, 2024)
Understanding patterns of plant-microbe interactions across plant species and populations is a critical yet poorly characterized aspect in the field of plant pathology.Microbial DNA sequences present as contaminants in omics data of plants obtained using next-generation sequencing methods provide a valuable source to explore the relationships among endophytic microbial diversity, disease and genetic differentiation of host plants, and environmental variation, but few such studies have been conducted. The flowering dogwood tree (Cornus florida L.), an ecologically important species in North America, is threatened by powdery mildew and dogwood anthracnose diseases, and knowledge of the microbial diversity harbored within genetically and environmental distinct populations of this species remains largely unknown. We conducted a metagenomics study utilizing the sequences of RAD-tag/genotype-by-sequence libraries from leaf tissues of C. florida to examine such host-fungus interactions across the dogwood's US range. Our data showed that microbial community composition significantly differed between visually healthy and diseased sites.Several microbial taxa known to interact with dogwood were identified from these sequences. We found no correlation between microbial diversity and relative abundances of sequences aligning to draft genomes of either pathogen causing powdery mildew or dogwood anthracnose. We found a significant relationship between differences of fungal communities and geographic distances of plant populations, suggesting roles of environments in shaping fungal communities in leaf tissues. Significant correlations between the genetic differentiation of plant samples and fungal community dissimilarity (beta diversity) were also observed in certain sets of our analyses-suggesting the possibility of a relationship between microbial community composition and plant genetic distance. This relationship persisted in significance even after controlling for significant effects of geographic-bioclimatic variation of microbial diversity. This suggests that genetics, in addition to the environment, play a significant role in shaping foliar fungal communities. These findings underscore the power of leveraging hidden microbial sequences within datasets originally collected for plant genetic studies to understand plant-pathogen interactions.